Estudo e modelagem 3D de um cabeçote para um motor monocilíndrico, 400cc, 4 T - Bruni, Paulo Henrique de Melo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The cylinder head contains the combustion chamber for the air-fuel mixture and the intake and exhaust valves, the valve guide and the valve seat. The cylinder head also is a support for the camshaft and valve rocker. The holes where the spark plugs are connected are designed to fit the better place in the combustion chamber. The cylinder heads often are manufactured using materials such as aluminum and cast iron. The cooling fins located in the outside of the cylinder head are designed for a good heat transfer and therefore their dimensions and positioning are important. This work aims the calculation for a cylinder head to be installed in a 400 cc displacement, gasoline powered, four stroke, single cylinder engine. According to the displacement it will be analyzed the combustion chamber, the intake and exhaust valves, as well as the camshaft and rocker arms. This also a work to help to accomplish the design of a single cylinder engine, where the alternatives parts, cylinder block and crankcase are all already machined and assembled in this campus

O cabeçote engloba a câmara de combustão para a mistura ar-combustível e contêm as válvulas de admissão e escape, os guias de válvulas e sede de válvula. O cabeçote também acomoda o suporte para o eixo de comando de válvulas e balancins. As aberturas onde as velas de ignição são rosqueadas no cabeçote são projetadas para melhor posicionamento da combustão. Os cabeçotes são normalmente fabricados de ligas de alumínio ou ferro fundido. As aletas de refrigeração na parte externa do cabeçote são projetadas para prover uma refrigeração eficiente e, portanto as suas dimensões são importantes.Este trabalho visa desenvolver os cálculos de um cabeçote para um motor de 400 cc, a gasolina e ciclo 4 tempos. De acordo com a cilindrada serão dimensionados a câmara de combustão, as válvulas de admissão e de escape, assim como os balancins e seus eixos. Este também é um trabalho complementar do projeto completo de um motor monocilíndrico, onde as partes alternativas, o cilindro, o volante e bloco já estão usinados e montados neste campus
Keywords: Motores; Cabeçotes (Maquinas-ferramenta); Imagem tridimensional; Single cylinder motor; 3D modeling